The first Olympics - Baglio, Ben M. (Toronto ; New York : Bantam, 1988)
You have travelled back to the ancient Olympic games and you are a competitor. What event will you participate in? You decide how the story will go.
5.5
3-6.
5-8
Keywords: Plot-your-own stories; Plot-your-own stories